Jenkins Fundamentals : Accelerate deliverables, manage builds, and automate pipelines with Jenkins /: Accelerate deliverables, manage builds, and automate pipelines with Jenkins. (2018) - Muli, Joseph; Okoth, Arnold
No abstract available